Consider the following grammar:
E → E+T | T
T → T*F | F
F → (E) | id
Draw a SLR state transition diagram for the above grammar. Also draw the SLR table.
STATE TRANSITION DIAGRAM:
FOLLOW(E)=FOLLOW(E')={),$}
FOLLOW(T)=FOLLOW(T')={+,),$}
FOLLOW(F)={*,+,),$}
SLR PARSING TABLE:
Show that no left recursive grammar can be LL(1). Show that no LL(1) grammar can be ambiguous.
For the input expression (4*7+1)*2, construct an annotated parse tree.
Write short notes on:
Discuss about Staffing
Explain the concept of frequency reuse in cellular systems.
Write the rules of DBA.
What are tunnelling and encapsulation in the context of mobile IP?